2007
DOI: 10.1007/s00015-007-1219-z
|View full text |Cite
|
Sign up to set email alerts
|

U-Pb SHRIMP zircon dating of andesite from the Dolomite area (NE Italy): geochronological evidence for the early onset of Permian Volcanism in the eastern part of the southern Alps

Abstract: The Athesian Volcanic District (AVD), a thick sequence of andesitic to rhyolitic lava and ignimbrite, overlies both the Variscan basement of the Dolomites and, where present, the continental basal conglomerate of Upper Carboniferous(?) to Early Permian age. This volcanic activity is known to mark the margin of the intra-Pangea megashear system between Gondwana and Laurasia, the onset age of which is determined in this study. SHRIMP U-Pb dating on zircon from Ponte Gardena/Waidbruck (Isarco/Eisack valley) basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
2
10
0
Order By: Relevance
“…Ludwig (1980); -, non-concordant age The oldest age group of 2,023 ± 31 Ma suggests the existence of a possibly early Proterozoic hinterland as already pointed out by Söllner and Hansen (1987). Similar age constrains in the Southern Alps were reported from basaltic andesites from Waidbruck by Visonà et al (2007) and from the quartzphyllite complex of Vetriolo by Klötzli (1999). Latter concluded that this age cannot directly be interpreted as a maximum sedimentation age, but represents detrital grains in the Vetriolo phyllite, originally derived from a Proterozoic basement.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Ludwig (1980); -, non-concordant age The oldest age group of 2,023 ± 31 Ma suggests the existence of a possibly early Proterozoic hinterland as already pointed out by Söllner and Hansen (1987). Similar age constrains in the Southern Alps were reported from basaltic andesites from Waidbruck by Visonà et al (2007) and from the quartzphyllite complex of Vetriolo by Klötzli (1999). Latter concluded that this age cannot directly be interpreted as a maximum sedimentation age, but represents detrital grains in the Vetriolo phyllite, originally derived from a Proterozoic basement.…”
Section: Discussionsupporting
confidence: 58%
“…The second group showing an U-Pb age of 882 ± 19 Ma has hardly been reported in the Southalpine basement so far and these ages are also very rare in the Alps. Visonà et al (2007) report a somewhat similar age of The youngest detrital zircons with an age of 638 ± 20 Ma can be interpreted to be maximum sedimentation ages. These are typical Cadomian (Pan-African) ages and occur widespread throughout the European Variscides.…”
Section: Discussionmentioning
confidence: 58%
“…The volcanic lava piles of the so-called Athesian Volcanism reach a thickness of about 2,000 m (D'Amico 1979). The volcanism started during the lower Permian (Cisuralian epoch) contemporaneously with the deposition of the Ponte Gardena conglomerates (290.7 ± 3 Ma, U-Pb zircon age, Visonà et al 2007b). In the central sector of the Athesian Volcanic Group the magmatic activity started with andesitic lava flows (286.0 ± 3.0 Ma, U-Pb zircon age, Avanzini et al 2010) and ended with the extrusion of rhyolitic ignimbrites associated with the formation of large calderas (275.0 ± 4.9 Ma, U-Pb zircon age, Avanzini et al 2010).…”
Section: Permian Magmatismmentioning
confidence: 99%
“…(Brixen), Cima d'Asta] with smaller satellite bodies [e.g., Chiusa (Klausen); Visonà et al 1987] and the associated volcanic products of the Athesian Volcanic District (Barth et al 1993;Visonà et al 2007b), and (b) of Triassic age represented by plutonic complexes (e.g., Predazzo-Monzoni, Bonadiman et al 1994;Visonà 1997) and by volcanic products (Barbieri et al 1982;Brack et al 2005).…”
mentioning
confidence: 98%
“…Three cycles of sedimentary successions and volcanics emplacement have been described from the lower Permian to Jurassic (see extended review in Marotta et al, ; Spalla et al, ). The first volcano‐sedimentary cycle (lower Permian) is characterized by a widespread volcanic activity in the whole Southalpine domain and part of the Helvetic and Penninic domains (Bussy, Sartori, & Thélin, ; Cannic, Lapierre, Monié, Briqueu, & Basile, ; Maino, Dallagiovanna, Gaggero, Seno, & Tiepolo, ), associated with continental clastic deposits (from conglomerates to siltites; Bargossi, Rottura, Vernia, Visonà, & Tranne, ; Bussien, Bussy, Masson, Magna, & Rodionov, ; Cadel, Cosi, Pennacchioni, & Spalla, ; Cassinis & Perotti, , ; Dallagiovanna, Gaggero, Maino, Seno, & Tiepolo, ; Gretter, Ronchi, Langone, & Perotti, ; Maino et al, ; Quick et al, ; Visonà, Fioretti, Poli, Zanferrari, & Fanning, ). The oldest volcanic products are 291‐Ma‐old andesites in the northern Dolomites (Visonà et al, ), 285‐ to 282‐Ma‐old volcanics in the Southalpine basins of the Central Alps (Zanoni & Spalla, ), and 291‐ to 285‐Ma‐old relict lamprophyre in the Antigorio nappe rocks of the Penninic domain of the Western Alps (Bussien et al, ).…”
Section: Tectonic Evolution and Metamorphic And Magmatic Recordsmentioning
confidence: 99%